The Influence of Influencer Marketing, Electronic Word of Mouth, and Brand Trust on Purchasing Decisions for Facetology Sunscreen in Generation Z - Rahayu, Tri Septin Muji; Aulia, Putri Rizky; Widyaningtyas, Dian; Fauziridwan, Meydy (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2025)
This study aims to examine the impact of influencer marketing, electronic word of mouth, and brand trust on the purchasing decisions of Facetology sunscreen among Generation Z in East Purwokerto. Data were collected through questionnaires targeting Generation Z in East Purwokerto. A purposive sampling method with a non-probability approach was used. Data analysis was conducted using multiple linear regression tests. Influencer marketing showed a positive but insignificant effect on purchasing decisions. In contrast, electronic word of mouth and brand trust had a significant positive influence on the purchasing decisions for Facetology Sunscreen.